2020
DOI: 10.1007/s00217-020-03489-w
|View full text |Cite
|
Sign up to set email alerts
|

Release of adsorbed ferulic acid in simulated gastrointestinal conditions

Abstract: Ferulic acid (FA) is a natural antioxidant with limited absorption when conjugated with biomolecules but whose free form is readily absorbed in the stomach and, to a lesser extent, in the ileum. The latter suffers from inflammation and oxidative stress, so a novel strategy for the delivery of FA in this compartment of the gastrointestinal tract was developed. Using the neutral un-functionalized resin Lewatit® VP OC 1064 MD PH, under optimized conditions, a loading of 144 mg FA/g of dry resin was obtained. By m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…It was reported that 25% of FA in tomatoes could be effectively absorbed. However, 5‐ O ‐feruloyl‐ l ‐arabinofuranose (FAA), a typical FA sugar ester in cereals, showed a lower absorption rate (Martins et al., 2020). Only 3% of FA from cereals and its metabolites were detected in urine, whereas 50% were tested upon free FA treatments (Lafay & Gil‐Izquierdo, 2007).…”
Section: Absorption and Metabolism Of Fa In Gastrointestinal Tractmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that 25% of FA in tomatoes could be effectively absorbed. However, 5‐ O ‐feruloyl‐ l ‐arabinofuranose (FAA), a typical FA sugar ester in cereals, showed a lower absorption rate (Martins et al., 2020). Only 3% of FA from cereals and its metabolites were detected in urine, whereas 50% were tested upon free FA treatments (Lafay & Gil‐Izquierdo, 2007).…”
Section: Absorption and Metabolism Of Fa In Gastrointestinal Tractmentioning
confidence: 99%
“…The resin has the ability to selectively adsorb FA from hydrolyzed complex matrices without the need for sugar co‐adsorption. The release of FA from the resin by the resin FA complex under the conditions found in the GI tract (e.g., pH changes) was evaluated (recovery of 22%) (Martins et al., 2020). The acidic medium promoted the adsorption of FA and impeded its release, whereas alkaline media caused the release of FA from the adsorbent and hindered its adsorption.…”
Section: The Intestinal Delivery Systems Of Famentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained formulation ensures the sustained release of the active substance [ 97 ]. Attempts have also been made to immobilize FA in the solid porous resin Lewatit ® , which provides the nanoparticles with narrow size distributions [ 98 ].…”
Section: Novel Strategies For Ferulic Acid Drug Deliverymentioning
confidence: 99%